Climate change mitigation in emerging economies: the case of Indonesia: hot air or leadership? - Jonas Hein (Deutsches Institut für Entwicklungspolitik (DIE), 2013)
It was at the climate change conference in Bali in 2007 (COP 13) that developing countries first agreed to initiate “nationally appropriate mitigation actions” (NAMA) in accordance with their respective capacities. At COP 15, in Copenhagen, developing countries submitted emissionreduction targets. Emerging economies, led by Indonesia and Brazil, committed to reducing their greenhouse gas emissions significantly below business as usual (BAU) by 2020. Mexico and the Dominican Republic have also recently passed climate laws. Indonesia ranks third after China and the United States in emitting greenhouse gases. This is mainly due to emissions from deforestation and peatland conversion. Since COP 13 Indonesia has sought to showcase itself as an active global leader in climate diplomacy. Despite quite low per capita emissions of around 2 tonnes of CO2 equivalents per year, the country announced plans to reduce its emissions up to 41 per cent below BAU by 2020. For achieving this target, Indonesia developed a detailed greenhouse gas reduction plan. Most of the emission reductions are planned to be achieved in the forestry and agriculture sectors. Anyhow, fossil fuel-based emissions from the transport and energy sectors are growing and might surpass land-based emissions after 2020. Indonesia's emission-reduction strategy is a good starting point for a transformation towards a low-carbon economy, especially in the land-use-related sectors. Planned activities such as the regional incentive scheme to promote climate-friendly activities and the domestic carbon market will go far beyond those implemented in many developed countries. However, the success of Indonesia's mitigation polices depends mainly on the ability to mobilise political capacities to overcome existing^barriers, which may hinder the transformation from a resource- and emission-intensive development path towards a more sustainable and long-term-orientated development path. Important steps to solve key challenges that would confirm the climate leadership claims of the Susilo Bambang Yudhoyono presidency are: a climate law adopted by The People's Representative Council (Parliament) would augment the domestic legitimacy and international credibility of Indonesia's mitigation efforts; a coherent BAU scenario that is third-party verified minimises the risk of virtual emission reductions (socalled hot air); incentives for local stakeholders are crucial for encouraging mitigation activities on the local level; the extension of the forest moratorium could contribute heavily to Indonesia's reduction targets.
Keywords: 330; Klimawandel; Landwirtschaft und ländliche Entwicklung